Ta’thir tatbiq wasilah Lungguhut fi tarqiyat dafi’iyyat ta’allum al-lughah al-‘arabiyyah lada tulab al-fasl al-thamin bi-madrasat al-mutawassitah al-islamiyyah al-ahliyyah Miftah al-Islah Tembiluk. - Allya Norratimah; Abdul Azis (An Nazhair: Journal of Arabic Education, 2026)
This study focuses on the effect of using the LingoHut application on improving Arabic language learning motivation among eighth-grade students at MTs Islamiyah Miftahul Ishlah Tembelok. The purpose of this study is to measure the effect of the LingoHut application on students’ motivation in learning Arabic and to determine the extent of its contribution to the level of learning motivation. The research employed a non-experimental method with a causal-associative design. The research sample was taken from class VIII A using the cluster sampling technique. Data were collected through a student perception questionnaire regarding the use of the LingoHut application and a learning motivation questionnaire covering the aspects of autonomy, competence, and relatedness. The results of data analysis showed a significance value of 0.000 < 0.05 and an r-value of 0.580, which is higher than the r-table value of 0.444, indicating that the alternative hypothesis was accepted. Furthermore, the coefficient of determination test revealed an R Square value of 0.336, indicating that the use of the LingoHut application contributes 33.6% to the improvement of students’ motivation in learning Arabic, while the remaining percentage is influenced by other factors beyond this study. The findings demonstrate that the use of the LingoHut application has a positive effect on the Arabic learning motivation of eighth-grade students at MTs Islamiyah Miftahul Ishlah Tembelok. Therefore, this study recommends the use of the LingoHut application as an interactive learning medium that can be applied in various educational contexts to support and enhance students’ learning motivation, particularly in Arabic language learning.